Analisis Upaya Pencegahan Obesitas Pada Anak-Anak - Muh. Wahyudin S. Adam; Nur Fadila Lukum; Marsya Mahabu; Yolanda Totoyi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Childhood obesity is a serious public health problem with significant long-term consequences. This study analyzes various efforts to prevent childhood obesity, including school-based, family-based, and community-based interventions. The study reviews various strategies, including behavioral modification, nutrition education, increased physical activity, and public policy interventions. The analysis shows that an integrated, multi-sectoral approach involving collaboration between schools, families, communities, and the government is key to successful childhood obesity prevention. Further research is needed to evaluate the effectiveness of various interventions and to develop more effective and sustainable strategies.